2017
DOI: 10.1016/j.jsv.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of de-correlating turbulence on the low frequency decay of jet-surface interaction noise in sub-sonic unheated air jets using a CFD-based approach

Abstract: In this paper we extend the Rapid-distortion theory (RDT)-based model derived by Goldstein, Afsar & Leib (J. Fluid Mech., vol. 736, pp. 532-569, 2013) for the sound generated by the interaction of a large-aspect-ratio rectangular jet with the trailing edge of a flat plate to include a more realistic upstream turbulence spectrum that possess a de-correlation (i.e. negative dip) in its space-time structure and use results from three-dimensional Reynolds-Averaged Navier-Stokes (RANS) solutions to determine the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Acoustic spectra have been calculated at three probe locations relatively close to the jet (in the nearfield). These probes are located at large angles with respect to the jet axis since it was observed that jet surface interaction noise dominates at large polar angles (see [39] for a study of AR8 nozzle and [20] where various rectangular nozzle jets were considered). The Ffowcs-Williams Hawkins surface is shown in Figure 9.…”
Section: Les Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic spectra have been calculated at three probe locations relatively close to the jet (in the nearfield). These probes are located at large angles with respect to the jet axis since it was observed that jet surface interaction noise dominates at large polar angles (see [39] for a study of AR8 nozzle and [20] where various rectangular nozzle jets were considered). The Ffowcs-Williams Hawkins surface is shown in Figure 9.…”
Section: Les Resultsmentioning
confidence: 99%
“…Far-field spectral results showed a large noise increase for low to mid frequencies due to upstream hydrodynamic waves in the jet that propagate along the plate, 'scrubbing' over the surface, until it reaches the trailing edge of the plate. (This is referred to as the 'gust solution' in Afsar et al [20]). As these waves interact with the trailing edge and the downstream turbulent mixing layer, they are scattered in the far-field as noise.…”
Section: Introductionmentioning
confidence: 99%
“…In figure 8, we show preliminary estimations of the noise radiation at three angles with respect to the jet axis. Jet surface interaction noise dominates at large polar angles (see Goldstein et al 8 for a study of AR8 nozzle and Afsar et al 1 where various rectangular nozzle jets were considered). Considering therefore the 90 degree spectrum in Fig.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…where D(u, ũ; θ) is the round jet directivity factor determined by application of the Wiener-Hopf technique (i.e., Equation ( 13) in Afsar et al [13]), y T = (y 2 , y 3 ) are transverse coordinates and,…”
Section: Summary Of the Mathematical Modeling Of Trailing-edge Noise And Defining The Objective Functionsmentioning
confidence: 99%
“…From an analytical and numerical standpoint, a lot of work has been done on this problem [10][11][12][13][14][15]. The discontinuity in the solid surface boundary condition can be treated formally using the Wiener-Hopf technique for a flat plate that is doubly infinite in the spanwise direction and lies parallel to the level curves of the streamwise mean flow.…”
Section: Introductionmentioning
confidence: 99%